Robust inference in partially linear models with missing responses - Bianco, Ana Maria (2014)
We consider robust testing on the regression parameter of a partially linear regression model, where missing responses are allowed. We derive the asymptotic behavior of the proposed test statistic under the null and contiguous alternatives. A numerical study is performed.